2022
DOI: 10.1128/jvi.00758-22
|View full text |Cite
|
Sign up to set email alerts
|

A SCID Mouse Model To Evaluate the Efficacy of Antivirals against SARS-CoV-2 Infection

Abstract: Unlike the ancestral SARS-CoV-2 strain, the Beta (B.1.351) variant of concern has been reported to replicate to some extent in WT mice (C57BL/6 and BALB/c). We demonstrate here that infection of SCID mice with the Beta variant resulted in high viral loads in the lungs on day 3 postinfection.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Our in vivo studies using K18-hACE2 mice resulted in a significant reduction of the SARS-CoV-2 lung viral loads in a lethal challenge model. The daily dose of α-DGN in these mice was 0.3 mg/kg (single dose therapeutic treatments, and once a day for prophylactic treatments), which is 1333- and 2000-fold lower than that of molnupiravir (200 mg/kg, twice a day) and nirmatrelvir (300 mg/kg, twice a day) employed in other studies via the IN route ( 31 ). In summary, we showed that α-DGN blocks SARS-CoV-2 infection at the step of cell binding, which may inhibit efficient cell-to-cell spread of the virus in lungs. Whether inhibition depends on binding of α-DGN to the host cell, to the virus, or both needs further investigation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our in vivo studies using K18-hACE2 mice resulted in a significant reduction of the SARS-CoV-2 lung viral loads in a lethal challenge model. The daily dose of α-DGN in these mice was 0.3 mg/kg (single dose therapeutic treatments, and once a day for prophylactic treatments), which is 1333- and 2000-fold lower than that of molnupiravir (200 mg/kg, twice a day) and nirmatrelvir (300 mg/kg, twice a day) employed in other studies via the IN route ( 31 ). In summary, we showed that α-DGN blocks SARS-CoV-2 infection at the step of cell binding, which may inhibit efficient cell-to-cell spread of the virus in lungs. Whether inhibition depends on binding of α-DGN to the host cell, to the virus, or both needs further investigation.…”
Section: Discussionmentioning
confidence: 92%
“…Our in vivo studies using K18-hACE2 mice resulted in a significant reduction of the SARS-CoV-2 lung viral loads in a lethal challenge model. The daily dose of α-DGN in these mice was 0.3 mg/kg (single dose therapeutic treatments, and once a day for prophylactic treatments), which is 1333-and 2000-fold lower than that of molnupiravir (200 mg/kg, twice a day) and nirmatrelvir (300 mg/kg, twice a day) employed in other studies via the IN route (31).…”
Section: Discussionmentioning
confidence: 92%
“…Antiviral efficacy of the combination of NTV and RTV, the two ingredients in the Paxlovid oral COVID-19 treatment, had until recently not been reported in animals, with initial reports focusing on high-dose (300 mg/kg) NTV alone ( 10 , 92 , 93 ). Recent studies tested the NTV + RTV combination for protection against severe disease at 150 + 10 mg/kg or at 200 + 50 mg/kg in K18-hACE2 mice ( 19 , 94 , 95 ) and at 125 + 83 mg/kg or 250 + 83 mg/kg in hamsters ( 96 ).…”
Section: Discussionmentioning
confidence: 99%
“…When we normalized the doses according to body surface areas in the individual species, they ranged from 6.25 to 3000 mg/m 2 bidaily. In four studies based on mouse models of COVID-19 including K18-hACE-2 mice, SCID mice, and lung-only mice, molnupiravir doses ranged from 20 to 500 mg/kg [38][39][40][41]. The studies in SCID mice and lung-only mice both found significantly reduced pulmonary viral titers accompanied by improved lung pathology [38,40].…”
Section: Dose Levels Of Molnupiravirmentioning
confidence: 99%
“…In four studies based on mouse models of COVID-19 including K18-hACE-2 mice, SCID mice, and lung-only mice, molnupiravir doses ranged from 20 to 500 mg/kg [38][39][40][41]. The studies in SCID mice and lung-only mice both found significantly reduced pulmonary viral titers accompanied by improved lung pathology [38,40]. In the study based on the lung-only mouse model, molnupiravir at 500 mg/kg twice daily (1500 mg/m 2 twice daily) was chosen, as this dose was assumed to provide intracellular 5 -triphosphate NHC levels similar to those in humans administered a dose of 1600 mg per day [40].…”
Section: Dose Levels Of Molnupiravirmentioning
confidence: 99%